Impact of Gluten on Irritable Bowel Syndrome - Uruj, Sana; Ali, Muhammad Zafar; Sarwar, Natasha; Hussain, Amina; Waseem, Muhammad (Pakistan Armed Forces Medical Journal, 2023)
Objective: To assess the impact of a gluten-free diet on the quality of life of patients managed for irritable bowel syndrome at a tertiary care hospitalStudy Design: Prospective comparative study.Place and Duration of Study: Department of Medicine/Gastroenterology, Pak Emirates Military Hospital, Rawalpindi Pakistan from Jul 2020 to May 2021.Methodology: Two hundred patients with irritable bowel syndrome and diagnosed on the basis of Rome-IV criteria were included in this study. They were divided into two groups via a lottery method. Group-1 received treatment as usual, depending upon the type of irritable bowel syndrome. Group-2 received treatment as usual and a gluten-free diet. Quality of life was assessed after one month using the World Health Organization Quality of Life-Brief scale.Results: Out of 200 patients with irritable bowel syndrome included in the study, 93(46.5%) were male, while 107(53.5%) were female. 125(62.5%) had good quality of life after one month of treatment, while 75(37.5%) had lesser quality of life. Statistical analysis revealed that irritable use of a gluten-free diet had a statistically significant relationship (p-value